National Health Interview Survey, 1993: AIDS Knowledge and Attitudes Supplement ([Verlag nicht ermittelbar], 1995)
The purpose of the National Health Interview Survey (NHIS) is to obtain information about the amount and distribution of illness, its effects in terms of disability and chronic impairments, and the kinds of health services people receive. This supplement includes variables from the NHIS core Person File (see NATIONAL HEALTH INTERVIEW SURVEY, 1993 [ICPSR 6534]), including sex, age, race, marital status, veteran status, education, income, industry and occupation codes, and limits on activity. Questions unique to this supplement cover sources of information on Acquired Immune Deficiency Syndrome (AIDS), perceptions of and discrimination against persons with AIDS, knowledge about modes of Human Immunodeficiency Virus (HIV) transmission, perceived likelihood of transmission by casual contact, experience with blood donation and HIV antibody testing, content of post-test counseling, and use of professional mental health counseling because of concern about AIDS.